Sedimentological data (XRF, calcimetry, spectrocolorimetry, insoluble fractions) of a calcareous tufa sequence from Pont de Joux, southeastern France - Naïs Sirdeys; Vincent Ollivier; Olivier Bellier; Jean-Pierre Bracco (PANGAEA, 2025)
We present data on elemental geochemistry (XRF), spectrocolorimetry, calcimetry, and insoluble fraction from six sedimentary tufa sequences spanning the Late Glacial and the Holocene periods. Between 2020 and 2023, calcareous tufa sequences were retrieved from the sites of the Thomassine (43.849687°, 5.753143°), the Jonquier (43.577439°, 6.216300°), the Pont de Joux (43.367381°, 5.615868°), and the Mirail Valley (MIR-1 -43.755237°, 5.547327°-, MIR-5 -43.789934°, 5.540534°-, and MIR-8 -43.790569°, 5.540395°), located in Provence, southeastern France. These records provide insights into environmental evolution, sedimentary dynamics, and local climatic trends through variations in sediment composition. All analyses conducted on these sequence samples (a total of 229 samples) were performed at LAMPEA (UMR 7269, Aix-Marseille University, CNRS), on the PlaSédO sedimentology platform (https://lampea.cnrs.fr/spip.php?article3853 ), part of the BOOST mutualized research platform (https://lampea.cnrs.fr/spip.php?rubrique211). Semi-quantitative elemental compositions were obtained using a Vanta C portable XRF (pXRF) analyzer on raw sediments previously dried at 50?°C for 24 hours. Major elements (Si, Ca, Al, Fe, K, Ti, Mg) are reported in weight percent; trace elements are reported in ppm, with detection limits noted (e.g., Mg not detected below 3000 ppm). Light elements (atomic number Z < 12) were excluded due to insufficient resolution, and major element contents were recalculated accordingly. Calcimetric measurements were performed using a FOGII™ portable digital calcimeter. The method involves measuring CO? pressure released during the reaction of 1?g of oven-dried, powdered sample with 5?mL of 6?M HCl. Results are expressed as weight percent CaCO? relative to the initial sample mass. The instrument was calibrated using 0.8?g of 99.1?% pure CaCO? standard, included automatic temperature correction, and provides a precision of ±0.1?%. Spectrocolorimetric measurements were conducted with a Konica Minolta CM-700d spectrocolorimeter with an 8 mm aperture. Samples were dried at 50?°C for 24 hours prior to analysis. The device was calibrated before each session using a white reference tile (CM-A182). Color parameters were recorded in the CIE Lab* space: L* indicates lightness (0 = black, 100 = white), a* represents the green–red axis, and b* the blue–yellow axis. L* is expressed as a percentage, while a and b* are dimensionless. Insoluble residue analysis was used to determine the quartz fraction in the tufa sequences. Approximately 25 g of dried (50?°C, 12 h), sieved (250–800 μm) sample was treated with 6 M HCl to remove carbonates. Residues were rinsed, dried, and sorted under polarized light to isolate quartz grains from organic and crystalline material. For samples with fewer than 30 grains, manual counting was performed from high-resolution images; for grain-rich samples, we used a wet image-sizing granulometer (Analysette 28 Fritsch ImageSizer) to determine grain count and morphometrics. Results are expressed as the number of quartz grains per 100 g of sediment. Radiocarbon data include new and sourced from previous studies. Ages are reported in uncalibrated units (ka BP) and were placed stratigraphically in agreement with the original authors. The sample heights are expressed in meters and refer to the height of the sample relative to the thalweg (reference level 0, which corresponds to the start elevation of the profile mentioned). These data constitute a valuable resource for understanding sedimentary and paleoenvironmental dynamics in the region and offer a robust foundation for climate modeling, reconstruction of sedimentary processes, and regional comparative studies.
In: Sirdeys, N et al. (2025): Sedimentological data (XRF, calcimetry, spectrocolorimetry, insoluble fractions) of six tardiglacial and holocene calcareous tufa profiles, southeastern France [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.986397